DIRECT COMPARISON OF INTERSECTING-TANGENTS VERSUS SECOND DERIVATIVE FOR DETERMINATION OF PULSE TRANSIT TIME AND PULSE WAVE VELOCITY. (June 2022) - Tairi, Amira; Obeid, Hasan; Fortier, Catherine; Paré, Mathilde; Côté, Nadège; Philibert, Emy; Garneau, Charles-Antoine; Duval, Karine; Groupil, Rémi; Agharazii, Mohsen
Abstract : Objective: Arterial stiffness is a non-traditional risk factor for cardiovascular disease. Aortic stiffness is assessed by determination of pulse wave velocity using pulse transit time and the distance between carotid and femoral arteries. Transit time is obtained by using the foot-to-foot method to define the transit time through intersecting tangents algorithm or the point of maximal upstroke during systole (2nd derivative). Millasseau et al have proposed a formula for converting transit time between methods using SphygmoCor (intersecting tangents) and the Complior Analyse (2nd derivative). Based on a mathematical modeling of the proposed formula, there is discrepancy between values of pulse wave velocities, especially in subjects with higher aortic stiffness. The objective of this study is to directly compare the two methods using the same pressure waveforms obtained by the newer generation of Complior Analyse and using Millasseau's formula. Design and method: In a cross-sectional study of heterogeneous subjects, aortic stiffness was assessed by the Complior Analyse device which uses 2nd derivative. The pulse waveforms were extracted and used for the analysis by custom MATLAB algorithm for intersecting tangents, and the results were compared to the formula proposed by Millasseau. Results: The preliminary results of the first 24 patients (men: 71%; mean age: 61 ± 18 years) show that Millasseau's formula underestimates the transit times values by about 19% in comparison with the transit times obtained by the intersecting tangents method using MATLAB software (49, 8 ± 18, 8 ms vs 61, 6 ± 18, 6 ms; P < 0, 001). This results in an overestimation of the pulse wave velocities values by about 30% (13, 8 ± 3, 8 m/s vs 10, 6 ± 2, 7 m/s; P < 0, 001). Conclusions: Our preliminary results allow us to conclude that the values of pulse wave velocities obtained with Millasseau's formula are overestimated values when comparing with values obtained by using the intersecting tangents method. Increasing the number of subjects will allow us to examine the possibility of a more reliable formula for converting transit times from one method to the other.